Effect of calcination cycles on the preparation of tin oxide based traditional drug: studies on its formation and characterization - Wadekar, M. P.; Rode, C. V.; Bendale, Y. N.; Patil, K. R.; Gaikwad, A. B.; Prabhune, Asmita (Journal of Pharmaceutical and Biomedical Analysis, 2006)
The preparation method of metal based Indian traditional drugs involves conversion of a pure metal into its oxide by repeated high temperature calcination cycles. In this work, the effect of number of calcination cycles followed in the preparation of tin oxide based Ayurvedic drug, `vanga bhasma' was studied by a systematic characterization of the drug samples after various calcination stages. It was found that tin was in the form of Sn4+ state and that the formation of SnO2 proceeded step-wise through Sn(OH)(4). (c) 2006 Elsevier B.V. All rights reserved.
Keywords: calcination cycles; Oxidation; oxidation state of tin; Particle size; tin oxide; vanga bhasma

Effect of cultural conditions and media constituents on production of penicillin V acylase and CTAB treatment to enhance whole-cell enzyme activity of rhodotorula aurantiaca (NCIM 3425) - Kumar, Atul; Singh, Sanjay; Poddar, Pankaj; Prabhune, Asmita; Pundle, Archana (Applied Biochemistry and Biotechnology, 2009)
Penicillin V acylase (PVA) is a pharmaceutically important enzyme as it plays a vital role in the manufacture of semi-synthetic beta-lactam antibiotics. Rhodotorula aurantiaca (NCIM 3425) produced high levels of intracellular penicillin V acylase after 18 h at pH 8.0 and temperature 27 degrees C. Fructose was the best carbon source for PVA production, whereas tryptone was the best nitrogen source to produce the enzyme up to 170 and 1,088 IU/l of culture, respectively. Additionally, the cell-bound PVA activity was enhanced on treatment with cationic detergent. Whole-cell activity was found to be doubled (204%) on treatment of 0.01 g dry weight of cells with 50 mu g/ml solution of N-cetyl-N,N,N-trimethylammoniumbromide at pH 8.0 for 1 h at room temperature. Atomic force microscopy images of permeabilized cells show perturbation in the cell wall and offer first-ever visual illustration of surface structure modifications that occur during permeabilization of R. aurantiaca cells leading to enhancement in activity of intracellular enzyme.
Keywords: Atomic force microscopy; Intracellular enzyme; Penicillin Vacylase; Permeabilization; Rhodotorula aurantiaca

Evaluation of ethanol production by a new isolate of yeast during fermentation in synthetic medium and sugarcane bagasse hemicellulosic hydrolysate - Hande, Aparna; Mahajan, Siddharth A.; Prabhune, Asmita (Annals of Microbiology, 2013)
A new xylose fermenting yeast was isolated from over-ripe banana by enrichment in xylose-containing medium. The phylogenetic analysis of ITS1-5.8S-ITS2 region sequences of ribosomal RNA of isolate BY2 revealed that it shows affiliation to genus Pichia and clades with Pichia caribbica. In batch fermentation, Pichia strain BY2 fermented xylose, producing 15 g l(-1) ethanol from 30 g l(-1) xylose under shaking conditions at 28A degrees C, with ethanol yield of 0.5 g g(-1) and volumetric productivity of 0.31 g l(-1) h(-1). The optimum pH range for ethanol production from xylose by Pichia strain BY2 was 5-7. Pichia strain BY2 also produced 6.08 g l(-1) ethanol from 30 g l(-1) arabinose. Pichia strain BY2 can utilize sugarcane bagasse hemicellulose acid hydrolysate for alcohol production, efficiency of fermentation was improved by neutralization, and sequential use of activated charcoal adsorption method. Percent total sugar utilized and ethanol yield for the untreated hydrolysate was 17.14% w/v and 0.33 g g(-1), respectively, compared with 66.79% w/v and 0.45 g g(-1), respectively, for treated hemicellulose acid hydrolysate. This new yeast isolate showed ethanol yield of 0.45 g g(-1) and volumetric productivity of 0.33 g l(-1) h(-1) from sugarcane bagasse hemicellulose hydrolysate detoxified by neutralization and activated charcoal treatment, and has potential application in practical process of ethanol production from lignocellulosic hydrolysate.
Keywords: D-xylose; Ethanol; Pichia; Sugarcane bagasse hemicellulose

Effect of pH on the hydrolytic kinetics of gamma-glutamyl transferase from bacillus subtilis - Balakrishna, Sharath; Prabhune, Asmita (Scientific World Journal, 2014)
The effect of pH on the steady state kinetics of gamma-glutamyl transferase (GGT) from Bacillus subtilis was examined using glutamyl-(3-carboxyl)-4-nitroanilide as the chromogenic reporter substrate. The enzyme was active in the pH range 7.0-11.0 with the optimum activity at pH 11.0. We noticed a pH dependent transformation in the nature of substrate consumption kinetics. The substrate saturation curves were hyperbolic in the pH range 7.0-9.0 but changed into sigmoid form at pH 10.0 and 11.0. Hill's coefficients were > 1. We also analysed the effect of pH on the structure of the enzyme. The circular dichroism spectra of the enzyme sample at pH 9.0 and 11.0 were coincidental in both far and near UV regions indicating conservation of the secondary and tertiary structures, respectively. Themolecular weight of the enzyme sample was the same in both pH 7.0 and 11.0 indicating conservation of the quaternary structure. These results show that the kinetic transformation does not involve significant conformational changes. Cooperative binding of multiple substrate molecules may not be the basis for the sigmoid kinetics as only one substrate binding site has been noticed in the reported crystal structures of B. subtilis GGT.

Evaluating the anticancer activity and nanoparticulate nature of homeopathic preparations of Terminalia chebula - Wani, Kirtee; Shah, Nilesh; Prabhune, Asmita; Jadhav, Arun; Ranjekar, Prabhakar; Kaul-Ghanekar, Ruchika (Homeopathy, 2016)
Background: Breast cancer is the most common cancer diagnosed among women and is the second leading cause of cancer death. Homeopathic medicines are part of the alternative medicines that are given as a supportive therapy in breast cancer. The objective of this study was to investigate the anticancer activity of commercially available homeopathic preparations of Terminalia chebula (TC) and evaluate their nanoparticulate nature. Methods: Mother tincture (MT) and other homeopathic preparations (3X, 6C and 30C) of TC were tested for their effect on the viability of breast cancer (MDAMB231 and MCF7) and non-cancerous (HEK 293) cell lines by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Cell growth assay was performed to analyze the effect of the different potencies on the growth kinetics of breast cancer cells. MT and 6C were evaluated for the presence of nanoparticles by using scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Results: MT decreased the viability of breast cancer (MDAMB231 and MCF7) and non-cancerous (HEK 293) cells. However, the other potencies (3X, 6C and 30C) decreased the viability of only breast cancer cells without affecting the viability of the non-cancerous cells. All the potencies, MT, 3X, 6C and 30C, reduced growth kinetics of breast cancer cells, more specifically at 1:10 dilution at 24, 48 and 72 h. Under SEM, MT appeared as a mesh-like structure whereas under TEM, it showed presence of nanoclusters. On the other hand, 6C potency contained 20 nm sized nanoparticles. Conclusion: The current study reports the anticancer activity of homeopathic preparations of TC against breast cancer and reveals their nanoparticulate nature. These preliminary results warrant further mechanistic studies at both in vitro and in vivo levels to evaluate the potential of TC as nanomedicine in breast cancer.

Effect of media components and growth conditions for improved linoleic acid production by beauveria species - Sanghi, Smrati; Chirmade, Tejas; More, Snehal; Prabhune, Asmita; Gupta, Vidya; Kadoo, Narendra (Journal of the American Oil Chemists Society, 2019)
Beauveria species are well-known insect pathogenic fungi, and Beauveria bassiana is used as a biopesticide against various pests in agriculture. However, the Beauveria species has not been reported as producers of microbial oils. In this study, Beauveria spp. MTCC 5184 was used to produce microbial oil with high linoleic acid (LA) content. Ten experiments were performed to evaluate the effects of several media parameters, such as carbon and nitrogen sources, pH, various concentrations of carbon and nitrogen, growth duration, and oleic acid (OLA) supplementation for maximum LA and dry biomass production by the fungus. Several of these parameters had a significant impact on the production of LA, as well as dry biomass. The glucose yeast extract (GYE) medium supplemented with 1.5% (w/v) peptone yielded maximum LA (0.32 +/- 0.01 g L-1) and biomass (5.51 +/- 0.26 g L-1). However, through the addition of 1.0% (w/v) OLA, the precursor of LA, LA production was enhanced 12-fold (1.24 +/- 0.03 g L-1), and the biomass production increased by 5-fold (11.05 +/- 0.46 g L-1) in comparison to those in the basal (GYE) medium. Using lactose as the sole carbon source produced the lowest LA (0.05 +/- 0.00 g L-1) and biomass (1.04 +/- 0.10 g L-1). The results of this study will be useful for the commercial exploitation of this fungus for the production of LA-rich microbial oil for use in the production of lubricants, greases, paints, cosmetics, etc.

Energy and life cycle impact assessment for xylitol production from corncob - Dasgupta, Diptarka; Sidana, Arushdeep; Ghosh, Prasenjit; Sharma, Tripti; Singh, Jasvinder; Prabhune, Asmita; More, Snehal; Bhaskar, Thallada; Ghosh, Debashish (Journal of Cleaner Production, 2021)
The conversion of biobased feedstocks into energy and value-added chemicals is one main approach to address the current global challenge for waste mitigation through the biorefinery mode. Corncob biomass which is one of the most abundant agricultural residue in India with a high hemicellulose content, can serve as a potential low-cost raw material for food-grade xylitol production. The present study demonstrates a process for xylitol production from corncob biomass with detailed energy and life cycle analysis for viability assessment. The major highlight of the process is the use of microbial fermentation, where biomass-derived D-xylose is converted to xylitol with high selectivity. Overall, 0.502 kg of xylitol crystals could be produced from 3.5 kg of corncob biomass. Simulation analysis revealed that the evaporators are the primary consumers of energy, and the process of heat integration can significantly reduce the energy requirements of the overall process. Environmental impacts of the system evaluated showed emission results of 8.68 kg CO2 equivalent and revealed that marine aquatic and freshwater eco-toxicity are the only possible contributors to the environment. The results suggest that the process would have favourable energy balances, which can be used in pilot plant and heat exchanger network design and operation for xylitol production scale up to 500 L. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: biomass valorization; Life cycle impact assessment; simulation; xylitol

Expression, purification and crystallization of Asrij, A novel scaffold transmembrane protein - Motiwala, Zenia; Darne, Priti; Prabhune, Asmita; Inamdar, Maneesha S.; Kulkarni, Kiran (Journal of Membrane Biology, 2021)
Asrij/OCIAD1 is a scaffold transmembrane protein belonging to the Ovarian Carcinoma Immunoreactive Antigen Domain containing protein family. In Drosophila and mouse models, Asrij localizes at the endosomal and mitochondrial membrane and is shown to regulate the stemness of hematopoietic stem cells. Interaction of Asrij with ADP Ribosylation Factor 1 (Arf1) is shown to be crucial for hematopoietic niche function and prohemocyte maintenance. Here, we report the heterologous expression, standardization of detergents and purification methodologies for crystallization of Asrij/OCIAD1. To probe the activity of bacterially expressed Asrij, we developed a protein complementation assay and conclusively show that Asrij and Arf1 physically interact. Further, we find that sophorolipids improve the solubility and monodispersibility of Asrij. Hence, we propose that sophorolipids could be novel additives for stabilization of membrane proteins. To our knowledge, this is the first study detailing methodology for the production and crystallization of a heterologously expressed scaffold membrane protein and will be widely applicable to understand membrane protein structure and function. Graphic
Keywords: Asrij/OCIAD1; Membrane protein crystallography; sophorolipids